The Analisis Strategi Pengembangan Wisata Lontar Sewu menggunakan Metode SWOT - Mujid Kurmidianata; Bagiyo Suwasono Bagiyo Suwasono (Jurnal Jaring SainTek, 2022)
This study aims to develop lake tourism by prioritizing of strenghts, weaknesses, opportunities and threats in the development of lake tourism located in Hendrosari Village, Gresik Regency. Which aims to optimize the potential that potential that exits in the lake to be used as a plate to find income because the tourism object is quite promising and the village community to developp and utilize these resources is very high. lake tour. In carrying out this development, the author will use several methods that will be used to determine the feasibility of developing lake tourism in hendrosari village, including the SWOT analysis method (Strenghts, Weaknesses, Opportunities and Threats).